Analisis Nilai Heroik dalam Novel Lolong Anjing di Bulan Karya Arafat Nur - Nurhiyasti, Mira; Yusuf, Yusri; Herman R, Herman R (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
The study is entitled "Analysis of Heroic Values in the Lolong Anjing di Bulanâ€™s Novel of Arafat Nur's Work". Heroic values or heroism is something that must be emulated. The problem of this research is how the heroic value contained in the novel Lolong Anjing di Bulan by Arafat Nur. This study aims to describe the heroic values in the novel Lolong Anjing di Bulan of Arafat Nur's work. The type of research used is qualitative research. The method used is descriptive qualitative method. The data source of this research is the novel Lolong Anjing di Bulan of Arafat Nur's work which was published in 2018. The data were analyzed using qualitative analysis techniques. Based on research that has been done, found 55 data that show the heroic value in the novel Lolong Anjing di Bulan by Arafat Nur which includes (1) courage values 17 data, (2) optimistic value 4 data, (3) abstinence value gives up 15 data, ( 4) the value of willingness to sacrifice 7 data, and (5) the value of the union of 12 data. Thus it can be concluded that the novel Lolong Anjing di Bulan Â written by Arafat Nur is full of heroic values or heroism. The results of research on these heroic values are expected to be used as a reference for people in a better social life.